Penggunaann e-LKPD Berbasis PjBL untuk Meningkatkan Kreativitas Siswa SMAN 3 Kota Jambi Melalui Pemanfaatan Limbah Organik Kulit Pisang dalam Materi Green Chemistry: Penelitian - Rinda Dwi Audia; Rayandra Asyhar; Isra Miharti (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Following the advancement of science and technology, human needs have also undergone significant development. This change is most apparent in the field of education, where demands on the quality, accessibility and relevance of learning are becoming increasingly complex and dynamic. The learning process is an interaction between teacher and student that aims to achieve these results, a learning tool is needed in the form of e-LKPD that displays interesting chemistry material with a paperless presentation, so that it can be accessed via smartphone, laptop, and other technology, making it more practical to use. This research is conducted to improve students creativity through the development and implementation of e-LKPD based on Project Based Learning (PjBL) that utilizes banana peel organic waste in learning Green Chemistry material and to understand the feasibility of e-LKPD conceptually and procedurally based in the National Board of Education (BSNP). This research is a development research that adapts the Hannafin & Peck development model. The instrument used for the research consisted of interview guidelines and questionnaires. The developed product was validated by material and media experts and evaluated by teachers, then individual and small group trials were conducted. The data analysis techniques used include quantitative data analysis and qualitative data analysis. The results showed that the trial was very feasible because the average score of the material expert was 4,6 (very feasible) and tge media expert was 4,7 (very feasible). In addition, based on the assessment of procedures by teachers obtained 4,5 (very feasible), the percentage of individual learner responses with a percentage of 93,9 % (very feasible) and small group 94,5 % (very feasible).